Dispensing Justice in Islam : Qadis and their Judgements - Masud, Muhammad Khalid; Peters, Rudolph; Powers, David (Brill Book Archive Part 1, ISBN: 9789004472495., 2005)
Dispensing Justice is designed to serve as a sourcebook of Islamic legal practice and qadi court records from the rise of Islam to modern times, drawing upon court records and qadi judgments, in addition to literary sources. In the first chapter, we survey the state of the field, sketching the history, structure, and modern transformation of the qadiship. The twenty chapters that follow are grouped thematically in four sections: (1) the nature and functions of the judgeship and its development over time; (2) the structure of the judicial apparatus; (3) the application of juristic thought and reasoning to specific cases in selected areas of the law; and (4) judicial procedure and the different forms of evidence. The volume fills a large gap in Islamic legal history.